1996
DOI: 10.1143/jjap.35.281
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation of all-trans-β-Carotene in Spin-Coated Film and in Langmuir-Blodgett Film as Detected by Polarized Optical Absorption and Reflection Spectroscopies

Abstract: The molecular orientation and spatial arrangement of all- trans-β-carotene in a spin-coated (SC) film and in a mixed Langmuir-Blodgett (LB) film with barium stearate (1:10) were studied by the use of polarized optical absorption and reflection spectroscopies at non-normal incidences. The newly applied analyses of these spectra show that the SC film is an amorphous film with density ρ=0.835 g/cm3, refractive index n=1.38 and extinction coefficient κ=1.09 at 445 nm. Based on the axis model proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
5
6
0
Order By: Relevance
“…The absorption spectrum of carotenoids is known to be affected by the interaction of carotenoid molecules with a solvent and by the interaction among the carotenoid molecules themselves [16,[29][30][31][32][33][34][35][36][37][38][39][40][41]. In the present study, the λ max values of carotenoids in the NoPL micelles showed a bathochromic shift compared to those in organic solvents.…”
Section: Discussionsupporting
confidence: 43%
“…The absorption spectrum of carotenoids is known to be affected by the interaction of carotenoid molecules with a solvent and by the interaction among the carotenoid molecules themselves [16,[29][30][31][32][33][34][35][36][37][38][39][40][41]. In the present study, the λ max values of carotenoids in the NoPL micelles showed a bathochromic shift compared to those in organic solvents.…”
Section: Discussionsupporting
confidence: 43%
“…An additional spectral broadening and a partial loss of the vibrational fine structure were detected in the spectrum of 16:0,18:1-PC. Hashimoto et al (34) reported increases in the spectral bandwidth along with increases of βcarotene aggregation levels. Therefore, in the present study, part of the β-carotene molecules may have aggregated in the micelle interior, particularly when it contained 16:0,18:1-PC, delaying β-carotene desorption from these micelles.…”
Section: Discussionmentioning
confidence: 99%
“…The UV-visible absorbance spectra of carotenoids are known to change according to the interactions between the carotenoid and its surrounding environment such as solvents (21), the interior of lipoprotein particles (33), and aggregated carotenoid molecules (34,35). The λ max is proportional to solvent polarizability, and thus to its refractive index (21).…”
Section: Discussionmentioning
confidence: 99%
“…Self-aggregation of carotenoid often takes place in aqueous organic solutions [154][155][156][157][158][159][160]. Carotenoid aggregates have also been observed in thin solid films [161][162][163] and in composite molecules [164,165]. Nevertheless, the self-assembly of fucoxanthin has not yet been reported.…”
Section: Photophysical Properties Of Molecular Aggregates Of Carotenoidsmentioning
confidence: 99%